A seawater-induced full-solid-waste concrete surface gradient composite corrosion-resistant layer and a forming method thereof
Patent Information
- Application Number
- CN202611201738.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-08-10
AI Technical Summary
[0009]本发明针对自然海水条件下混凝土表面沉积层形成过程缓慢、层体结构难以控制,难以抵御海水中侵蚀离子的侵蚀作用之问题,提供一种海水诱导的全固废混凝土表面梯度复合抗蚀层及其形成方法
[0028]与仅依靠自然海水浸泡形成表面沉积层的方式相比,本发明至少具有以下有益效果。
Smart Images

Figure CN122685442B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of surface protection technology for marine engineering materials, and particularly relates to a gradient composite anti-corrosion layer for the surface of seawater-induced solid waste concrete for marine or coastal structures and its formation method; specifically, it relates to a gradient composite anti-corrosion layer for the surface of a seawater-induced solid waste concrete substrate, and a method for forming the gradient composite anti-corrosion layer in situ using acidic surface activation, alkaline interface regulation and bicarbonate mineralization treatment. Background Technology
[0002] Concrete in marine environments is subjected to the combined effects of chloride ions, sulfate ions, magnesium ions, and wet-dry cycles over a long period. Corrosive ions in seawater can migrate into the concrete through pores and microcracks, causing problems such as decalcification of hydration products, sulfate reactions, magnesium salt corrosion, and steel reinforcement corrosion.
[0003] On the other hand, with the increasing development of environmental protection, the application of all-solid-waste concrete is becoming more and more widespread. For all-solid-waste concrete with slag, carbide slag, industrial by-product gypsum, silica fume and tailings as the main raw materials, its cementing system, pore solution composition and unreacted particle content are different from ordinary silicate cement concrete. The surface reaction process and spatial distribution of reaction products under the action of seawater are also different.
[0004] Existing conventional marine concrete protection technologies typically include reducing the water-cement ratio, incorporating mineral admixtures, applying organic or inorganic surface coatings, and surface treatments using silane impregnation, polymer coating, or cement-based penetrating crystallizing materials. While these methods can reduce the migration of corrosive ions to some extent, some require additional coatings with compositions different from the concrete matrix, leading to issues such as interfacial compatibility, long-term bond stability, and difficulty in repairing localized damage.
[0005] Previous studies have shown that when concrete comes into contact with seawater, the OH- in the pore solution of the concrete increases. - It can increase the local pH at the concrete-seawater interface, thereby reducing the amount of magnesium in the seawater. 2+ Precipitation forms Mg(OH)2; simultaneously, Ca is released from the concrete. 2+ It can react with bicarbonate or carbonate ions in seawater to form calcium carbonate deposits. Therefore, a sedimentary layer mainly composed of Mg(OH)2 and calcium carbonate may form on the concrete surface. However, this type of sedimentation process mainly depends on the natural marine environment. In coastal erosion environments, the formation rate of Mg(OH)2 and calcium carbonate is significantly slower than the migration rate of erosion ions. The concrete surface cannot form a dense anti-corrosion layer to resist the erosion of concrete by erosion ions in seawater, and interface control is usually not performed for solid waste concrete containing a large number of unreacted slag particles.
[0006] In particular, existing technologies typically treat the Mg(OH)₂ layer as a common precipitate layer formed on the concrete surface or in surface pores, failing to fully utilize this deposit as an interface for subsequent carbonate mineralization and the growth of multi-component inorganic reactive phases. Furthermore, existing technologies do not fully leverage the characteristics of solid waste concrete surface matrix—which can be activated, unreacted slag particles can be exposed or partially detached, and slag can continuously provide reactive components such as Ca, Si, and Al—and lack a repeatable method for controlling the following gradient structure: a continuous intermediate layer of brucite containing or separating unreacted slag particles near the matrix, and an outer reactive layer containing the calcium carbonate phase and the second inorganic reactive phase on the seawater side. This gradient structure holds promise for reducing the ability of corrosive media such as chloride, sulfate, and magnesium ions to migrate into the matrix through surface pores and microcracks.
[0007] In addition, while simply extending the seawater immersion time may produce scattered surface deposits, it is difficult to obtain a composite anti-corrosion layer with a specific sequence, particle encapsulation or isolation structure and elemental gradient within the time allowed by the project due to the lack of control over the degree of surface activation, interfacial alkalinity and bicarbonate supply process.
[0008] Therefore, it is necessary to provide a method for treating the surface of solid waste concrete, which involves staged control of the substrate surface state, interfacial alkalinity, and bicarbonate supply to reduce the Mg content in seawater. 2+ It reacts synergistically with the Ca, Si, and Al components released or provided by the solid waste concrete to form a structurally controllable gradient composite anti-corrosion layer on the surface of the solid waste concrete. Summary of the Invention
[0009] This invention addresses the problems of slow formation of sedimentary layers on concrete surfaces under natural seawater conditions, difficulty in controlling the layer structure, and inability to resist the corrosive effects of seawater ions. It provides a seawater-induced gradient composite anti-corrosion layer on the surface of all-solid-waste concrete and its formation method. This marine concrete protection technology has advantages such as low cost, low maintenance cost, and significantly improved durability of concrete structures, making it of great significance for the protection of marine engineering structures.
[0010] Based on the seawater-induced environment, this invention sequentially applies acid activation, alkaline treatment, and bicarbonate treatment to the surface of solid waste concrete, thereby regulating the surface reaction space, Mg(OH)2 precipitation environment, and outer carbonate mineralization process, so that a gradient composite anti-corrosion layer including a magnesia intermediate layer and a dense outer reaction layer is formed on the surface of solid waste concrete.
[0011] On the one hand, the present invention provides a seawater-induced gradient composite anti-corrosion layer on the surface of a solid waste concrete substrate. The seawater-induced gradient composite anti-corrosion layer on the surface of the all-solid-waste concrete substrate includes, sequentially along the direction from the all-solid-waste concrete substrate toward the seawater side: The intermediate layer of brucite includes a continuous brucite phase and unreacted slag particles distributed in the continuous brucite phase, at least some of the unreacted slag particles are at least partially surrounded by the continuous brucite phase, and / or at least some of the unreacted slag particles are separated from the solid waste concrete matrix by the continuous brucite phase. And an outer reaction layer, which is located on the seawater side of the brucite intermediate layer and includes a calcium carbonate phase and a second inorganic reaction phase.
[0012] In a further technical solution, at least some of the unreacted slag particles have their entire outer surface surrounded by a continuous brucite phase. Specifically, this structure should be confirmed by continuous slicing, three-dimensional reconstruction, or other characterization methods that can demonstrate the three-dimensional embedding state of the particles. When using two-dimensional cross-sectional characterization, the structure can be described as the unreacted slag particles having their periphery surrounded by a continuous brucite phase on the cross-section.
[0013] In a further technical solution, the outer reaction layer contains Ca, Mg and Al elements.
[0014] In a further technical solution, the calcium carbonate phase includes at least one of aragonite and calcite.
[0015] In a further technical solution, the second inorganic reaction phase includes at least one of a calcium-silicon-aluminum inorganic reaction phase, a magnesium-aluminum inorganic reaction phase, and a calcium-aluminum inorganic reaction phase. Specifically, the second inorganic reaction phase includes at least one of CASH gel, magnesium-aluminum layered bimetallic hydroxide, and calcium-aluminum layered bimetallic hydroxide.
[0016] In a further technical solution, the all-solid-waste concrete matrix is made of all-solid-waste cementitious materials, solid-waste aggregates, and water. Taking the total dry weight of the all-solid-waste cementitious materials as 100%, the all-solid-waste cementitious materials include: 5-10% calcium carbide slag; 20-30% industrial by-product gypsum; 5-20% silica fume; and the remainder is slag.
[0017] In a further technical solution, the industrial by-product gypsum can be selected from one or both of desulfurized gypsum and phosphogypsum.
[0018] In a further technical solution, the solid waste aggregate includes solid waste fine aggregate.
[0019] In a further technical solution, the solid waste fine aggregate can be selected from one or more of iron tailings sand, river dredging sand and gold mine tailings sand, and the solid waste fine aggregate accounts for 10 to 30% of the total mass of all dry solid raw materials in the solid waste concrete matrix.
[0020] In a further technical solution, the solid waste aggregate also includes solid waste coarse aggregate.
[0021] On the other hand, the present invention also provides a method for forming the above-mentioned seawater-induced gradient composite anti-corrosion layer, comprising the following steps: S1, Acidic Surface Activation and First Stage Seawater Curing: Prepare a solid waste concrete matrix. After the solid waste concrete matrix has set, spray a dilute sulfuric acid solution with a pH of 2.5 to 3.0 onto the surface to be treated and allow the dilute sulfuric acid solution to react with the surface to be treated for 6 hours. Subsequently, the solid waste concrete matrix is placed in natural seawater for the first stage of soaking and curing, which lasts for 1 to 3 days; this creates a surface microcrack reaction zone within a preset depth from the surface to be treated, and weakens or breaks the continuous solid phase connection between at least some unreacted slag particles and the surrounding matrix. S2, Alkaline Interface Regulation and Second Stage Seawater Conservation: After the first stage of soaking and curing is completed, the solid waste concrete substrate is taken out of the natural seawater and an alkaline treatment solution containing calcium hydroxide is sprayed onto the surface to be treated. Subsequently, the solid waste concrete matrix was placed back into natural seawater for a second stage of soaking and curing, which lasted for 7 to 14 days. The alkaline treatment solution increases the local alkalinity at the concrete-seawater interface, thereby reducing the amount of Mg in the seawater. 2+ A continuous Mg(OH)2 phase is formed in the surface microcrack reaction zone, and at least some unreacted slag particles are at least partially surrounded by the continuous Mg(OH)2 phase or separated from the solid waste concrete matrix, forming the magnesia intermediate layer. S3, Bicarbonate Treatment and Third Stage Seawater Conservation: After the second stage of soaking and curing is completed, a sodium bicarbonate solution with a concentration of 0.01 to 0.05 mol / L is sprayed onto the surface of the solid waste concrete substrate that forms the brucite intermediate layer. Then, a third stage of seawater soaking and curing is carried out for 7 to 14 days, forming an outer reaction layer including a calcium carbonate phase and a second inorganic reaction phase on the seawater side of the brucite intermediate layer.
[0022] In the specific technical solution, sodium bicarbonate solution provides bicarbonate ions for the mineralization of the outer carbonate layer, forming an outer reaction layer including a calcium carbonate phase and a second inorganic reaction phase on the seawater side of the brucite intermediate layer, ultimately obtaining a seawater-induced gradient composite anti-corrosion layer.
[0023] In a further technical solution, in step S1, a surface microcrack reaction zone is formed at a distance of 0 to 10 μm from the surface of the solid waste concrete matrix. The surface microcrack reaction zone contains at least one of ettringite and gypsum, and can cause some unreacted slag particles to lose their solid-phase continuous connection with the surrounding matrix.
[0024] In a further technical solution, the alkaline treatment solution containing calcium hydroxide is selected from at least one of saturated quicklime solution and supernatant of carbide slag slurry.
[0025] In a further technical solution, the seawater referred to in this invention can be natural seawater or simulated seawater prepared according to the main ionic composition of natural seawater in the target sea area; the seawater contains at least Mg. 2+ SO4 2- and HCO3 - and CO3 2- At least one of the following. When using simulated seawater, it is preferable to determine the main ion concentration, liquid-to-solid ratio, temperature, and liquid exchange cycle based on actual measurements of natural seawater.
[0026] In a further technical solution, the first stage of soaking and curing can be static soaking; the second stage of soaking and curing can be static soaking, or soaking with a low flow rate of seawater velocity greater than 0 and not higher than 0.3 m / s; the third stage of soaking and curing can be static soaking, or soaking with a low flow rate of seawater velocity greater than 0 and not higher than 0.3 m / s.
[0027] In a further technical solution, step S1 involves preparing a solid waste concrete matrix: taking 5-10% of the total dry weight of the solid waste cementitious material as 100%, weighing 20-30% of carbide slag, 20-30% of industrial by-product gypsum, 5-20% of silica fume, and the remainder of slag, and dry mixing them to ensure uniform dispersion of the powder components; adding solid waste aggregate and continuing mixing to ensure that the fine solid waste aggregate accounts for 10-30% of the total dry solid raw material weight; then adding water and stirring; and finally filling the mixture into a mold for molding.
[0028] Compared with the method of forming a surface deposit layer by simply relying on natural seawater soaking, the present invention has at least the following beneficial effects.
[0029] (1) The present invention uses acidic surface activation treatment to regulate the reaction space of the surface layer of solid waste concrete, which is beneficial to expose the unreacted slag particles on the surface and provide reaction sites for the formation of subsequent inorganic deposition phases.
[0030] (2) This invention adjusts the local alkalinity of the concrete-seawater interface by using an alkaline treatment solution containing calcium hydroxide, thereby promoting the growth of Mg in seawater. 2+ It is converted into Mg(OH)2, causing Mg(OH)2 to evolve from a dispersed precipitate to a continuous phase structure.
[0031] (3) The continuous phase of brucite can encapsulate or isolate some unreacted slag particles, making the resulting brucite intermediate layer different from the ordinary Mg(OH)2 precipitate layer formed only in the original concrete pores.
[0032] (4) The present invention promotes the carbonate mineralization of the seawater side of the brucite intermediate layer by bicarbonate treatment, and uses the Ca, Si and Al components provided by the slag particles and the all-solid waste cementation system to form a second inorganic reaction phase, thereby forming a gradient composite structure that transitions from the brucite intermediate layer to the outer reaction layer.
[0033] (5) The intermediate layer and the outer reaction layer of the magnesia stone work together to form a dense surface anti-corrosion layer, which reduces the surface pores of the solid waste concrete, can prolong the migration path of corrosive ions in seawater into the interior of the solid waste concrete, and reduce the transmission effect of surface interconnected pores and microcracks on the corrosive medium.
[0034] (6) The composite anti-corrosion layer of the present invention is mainly formed by the reaction of seawater ions, the components of solid waste concrete itself, and inorganic treatment agents, and belongs to the inorganic reactive anti-corrosion layer. Compared with organic coatings that rely on continuous polymer film formation to form a physical barrier, the present invention does not rely on the polymer film formation and curing process; the anti-corrosion layer is generated in situ from the concrete surface to the interior, and forms a gradient transition in composition and structure with the substrate, which is beneficial to improving the interfacial compatibility and bonding strength between the anti-corrosion layer and the concrete substrate, reducing the risk of interface debonding, cracking or peeling of simple adhesive coatings, thereby improving the service stability of the anti-corrosion layer in the marine environment. Attached Figure Description
[0035] Figure 1 This is a backscattered electron microscope combined with energy dispersive spectroscopy scan of the cross section of the specimen in Example 1.
[0036] Figure 2 This is a thermogravimetric analysis diagram of the substrate and surface of the specimen in Example 1.
[0037] Figure 3 This is the infrared spectrum analysis diagram of the composite anti-corrosion layer in Example 1.
[0038] Figure 4 This is a backscattered electron microscope combined with energy dispersive spectroscopy line scan of the cross section of the specimen in Example 3.
[0039] Figure 5 This is a backscattered electron microscope combined with energy dispersive spectroscopy (EDS) scan of the cross-section of specimen 1 in Comparative Example 1.
[0040] Figure 6 This is a comparison chart of thermogravimetric analysis of specimen 1 and specimen 1 of Example 1.
[0041] Figure 7 These are backscattered electron microscope images combined with energy dispersive spectroscopy scans of Example 1 and Comparative Example 3. Detailed Implementation
[0042] The present invention will be further described below with reference to specific embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention.
[0043] I. Terminology Explanation The "all-solid-waste cementitious material" referred to in this invention means that the dry solid components in the cementitious material are all derived from industrial solid waste or industrial by-products, and its specific components are described below.
[0044] The "brucite continuous phase" referred to in this invention refers to an inorganic phase with Mg(OH)₂ as the main phase and continuously distributed within the observation area. The brucite continuous phase can be identified by X-ray diffraction or Fourier transform infrared spectroscopy, and its continuous distribution can be confirmed by combining cross-sectional electron microscopy images.
[0045] The term "unreacted slag particles" in this invention refers to slag particles that retain their original morphology after seawater curing or have not been completely converted into hydration reaction products. Unreacted slag particles can be identified through a combination of backscattered electron imaging, elemental composition, and particle morphology.
[0046] The term "loss of solid phase continuity with the matrix" in this invention refers to the absence of a continuous path directly connecting the unreacted slag particles and the solid waste concrete matrix through the original matrix solid phase. Instead, the two are separated by a continuous phase of magnesia, pores, or other newly generated reactive phases.
[0047] The phrase "the outer reaction layer as a whole contains Ca, Mg and Al elements" in this invention means that Ca, Mg and Al can be detected simultaneously in multiple representative regions of the outer reaction layer, without requiring that each individual phase contains all three elements simultaneously.
[0048] 2. Raw materials Before use, calcium carbide slag undergoes drying, crushing, and screening. Calcium carbide slag is primarily used to provide alkaline calcium components.
[0049] The slag used is granulated blast furnace slag powder. The slag contains reactive Ca, Si, and Al components, and allows some unreacted slag particles to remain after the cementitious material hardens.
[0050] Industrial by-product gypsum is selected from desulfurized gypsum, phosphogypsum, or a mixture of both. Before use, the industrial by-product gypsum should be converted to a dry basis mass according to its moisture content.
[0051] Silica fume is used to provide active silica components and adjust the particle size distribution of the cementing system.
[0052] The solid waste fine aggregate uses iron tailings sand, river dredging sand, or gold mine tailings sand. The solid waste fine aggregate is dried and screened before use, and its particle size ranges from 0.1 to 2.36 mm.
[0053] III. Preparation of All-Solid Waste Concrete Matrix With the total dry weight of all solid waste cementitious materials as 100%, weigh out 5-10% carbide slag, 20-30% industrial by-product gypsum, 5-20% silica fume, and the remainder slag.
[0054] The above-mentioned cementitious materials are dry-mixed to ensure uniform dispersion of all powder components. Solid waste fine aggregates, comprising 10-30% of the total mass of all dried solid raw materials, are then added and mixed further.
[0055] Then add water and stir. The water-to-gel ratio is in the range of 0.12 to 0.8, and the stirring time is 2 minutes.
[0056] The mixture is poured into a mold and shaped. After reaching the final set state, it is demolded or the surface to be treated is retained for subsequent processing. The final set time is determined according to the actual gelling system.
[0057] IV. Preparation of the treatment solution 1. Dilute sulfuric acid solution Sulfuric acid was diluted with water to prepare a dilute sulfuric acid solution with a pH of 2.5–3.0. During preparation, the sulfuric acid was slowly added to the water, and the pH was measured after the solution cooled to ambient temperature.
[0058] 2. Saturated solution of quicklime Add excess quicklime to the water and stir thoroughly to retain undissolved Ca(OH)2 in the system. After standing, take the clear upper layer as the saturated quicklime solution.
[0059] 3. Supernatant from carbide slag slurry Carbide slag is mixed with water to form carbide slag slurry. The mixture is stirred and allowed to stand to separate into layers. The clear liquid at the top is taken as the supernatant of the carbide slag slurry.
[0060] 4. Sodium bicarbonate solution Sodium bicarbonate is added to water to prepare a sodium bicarbonate solution with a concentration of 0.01–0.05 mol / L. The solution is preferably prepared and sealed before use to minimize changes in solution composition due to CO2 exchange.
[0061] V. General Formation Methods Step 1: Acidic surface activation and first-stage seawater conditioning After the solid waste concrete matrix has set, remove the laitance and loose particles from the surface to be treated. Spray a dilute sulfuric acid solution with a pH of 2.5–3.0 evenly onto the surface to be treated, so that the surface is wetted with the dilute sulfuric acid solution.
[0062] The spraying rate of dilute sulfuric acid solution is 0.5–2 L / m², and the number of sprays is 1–3. Allow the dilute sulfuric acid solution to react with the surface to be treated for 6 hours. After acid treatment, rinse with clean water or seawater.
[0063] The solid waste concrete substrate was then placed in natural seawater for the first stage of immersion curing, which lasted for 1 to 3 days.
[0064] Dilute sulfuric acid can react with the alkaline calcium-containing phase and carbonate phase on the surface of the matrix, causing controlled dissolution of the surface and providing SO4. 2- Under the subsequent influence of seawater and an alkaline environment, a reaction zone containing gypsum or ettringite can form on the surface. The above mechanism is used to explain the surface reaction process and does not imply that all embodiments must form reaction products with the same content or spatial distribution.
[0065] Step 2: Alkaline interface regulation and second-stage seawater conditioning to form the brucite intermediate layer. After the first stage of soaking and curing, the solid waste concrete substrate is removed from the natural seawater. Free water on the surface to be treated is removed without damaging the surface reaction zone formed in the first stage.
[0066] Spray an alkaline treatment solution containing calcium hydroxide evenly onto the surface to be treated. The spraying rate of the alkaline treatment solution per unit area is 0.5–2 L / m², the number of sprays is 1–3, and the contact time is 0.5–1 hour.
[0067] The solid waste concrete substrate was then placed back into natural seawater for a second stage of soaking and curing, which lasted for 7 to 14 days.
[0068] Alkaline treatment solution increases OH- ions near the interface - Activity, which affects the Mg content in seawater. 2+ The reaction occurs according to the following formula: Mg 2+ +2OH - →Mg(OH)2↓ The Mg(OH)2 formed precipitates in the surface microcrack reaction zone and gradually connects to form a continuous phase. Some unreacted slag particles that have lost solid-phase continuity with the original matrix are separated or embedded by the Mg(OH)2 continuous phase, forming a brucite intermediate layer.
[0069] Step 3: Bicarbonate treatment and third-stage seawater conditioning to form an outer reaction layer. After the second stage of soaking and curing is completed, the solid waste concrete substrate is removed from the natural seawater, and the free water on the surface to be treated is removed.
[0070] A sodium bicarbonate solution with a concentration of 0.01–0.05 mol / L is uniformly sprayed onto the surface to be treated. The spraying rate of sodium bicarbonate solution per unit area is 0.5–2 L / m², the number of sprays is 1–3, and the contact time is 0.5–1 hour.
[0071] The solid waste concrete substrate was then placed back into natural seawater for a third stage of soaking and curing, which lasted for 7 to 14 days.
[0072] Bicarbonate ions participate in carbonate equilibrium in the interfacial environment and react with Ca. 2+ The reaction that forms the calcium carbonate phase can be represented as follows: Ca 2+ +CO3 2- →CaCO3↓ Unreacted slag particles and their adjacent reactive phases in the brucite mesosphere can continue to provide Ca, Si, and Al components. Under suitable interfacial chemical conditions, these components can participate in the formation of CASH gel, magnesium-aluminum layered bimetallic hydroxide, or calcium-aluminum layered bimetallic hydroxide, thereby forming an outer reactive layer on the seawater side of the brucite mesosphere.
[0073] The technical solution of the present invention will be further illustrated below through examples and comparative examples. The raw material quality, treatment liquid volume, time, and flow rate given in each example are representative and executable conditions, and should not be construed as limiting the scope of protection of the present invention.
[0074] VI. Examples and Comparative Examples (I) Example 1: Weigh out 0.7 kg of calcium carbide slag, 2.5 kg of desulfurized gypsum, 1 kg of silica fume, and 5.8 kg of slag by dry basis to obtain 10 kg of all-solid-waste cementitious material. Add 2.5 kg of iron tailings sand, so that the solid waste fine aggregate accounts for 20% of the total mass of all dry solid raw materials; add 1.7 kg of water, with a water-cement ratio of 0.17. Dry mix all powders and iron tailings sand evenly, add water and stir for 2 min, mold and cure until final set to obtain all-solid-waste concrete matrix specimens.
[0075] A dilute sulfuric acid solution with a pH of 2.8 was sprayed onto the surface to be treated in two applications, with a total spraying volume of 1.0 L / m². 2 After spraying, allow the solution to fully wet the surface and react for 6 hours. After gently rinsing with seawater, place the specimen in natural seawater for static immersion for 3 days.
[0076] Remove the specimen and remove surface free water. Spray with a saturated quicklime solution twice, with a total spraying rate of 1.0 L / m³. 2 After contact for 45 minutes, it is placed back into natural seawater for static soaking for 14 days.
[0077] The specimen was then removed and sprayed once with a 0.01 mol / L sodium bicarbonate solution, for a total spraying volume of 0.5 L / m³. 2 After being exposed to seawater for 30 minutes, the sample was statically immersed in natural seawater for 10 days to obtain a seawater-induced gradient composite anti-corrosion layer on the surface of the solid waste concrete matrix, which is the specimen of Example 1.
[0078] In Example 1, cross-sectional samples were taken from the outer surface to the interior of the matrix. Backscattered electron microscopy combined with energy dispersive spectroscopy (EDS) was used to observe the continuity of the layers, the connection between unreacted slag particles and the matrix, and the distribution of Ca, Mg, Si, and Al elements along the depth direction. Figure 1 As shown. Thermogravimetric analysis was performed on samples from the substrate and surface of the specimen from Example 1, as follows... Figure 2 As shown, a significant increase in the thermal decomposition peak of brucite is observed, indicating the formation of a brucite phase on the matrix surface. However, due to the low concentration of sodium bicarbonate solution, the outer reaction layer is not obvious; its presence is only observed through the EDS distribution of Ca, indicating that sodium bicarbonate mineralization is necessary. Figure 3 The image shows the infrared spectrum analysis of the composite anti-corrosion layer of the specimen in Example 1. The image shows characteristic peaks of the calcium carbonate phase, including calcite and aragonite, as well as a second inorganic reactive phase, including CASH gel and calcium-aluminum layered bimetallic hydroxide.
[0079] (II) Example 2: Lower limit ratio, supernatant of calcium carbide slag slurry and low flow rate seawater curing Weigh out 0.8 kg of calcium carbide slag, 2 kg of phosphogypsum, 0.5 kg of silica fume, and 6.7 kg of slag on a dry basis to obtain 10 kg of all-solid waste cementitious material. Add 1.765 kg of gold ore tailings sand to make the solid waste fine aggregate account for 15% of the total mass of all dry solid raw materials; add 1.7 kg of water, with a water-cement ratio of 0.17, and stir, mold, and cure until final set according to the method in Example 1.
[0080] Spray a dilute sulfuric acid solution with a pH of 2.5 onto the surface to be treated at a rate of 0.5 L / m². 2 After reacting for 6 hours, the sample was gently rinsed with seawater and then statically soaked in natural seawater for 1 day. After removing the sample, it was sprayed with 0.5 L / m³ of supernatant from the carbide slag slurry. 2 After contact for 30 minutes, it was then soaked in natural seawater with a flow rate of 0.1 m / s for 7 days. Subsequently, it was sprayed once with 0.5 L / m of 0.01 mol / L sodium bicarbonate solution. 2 After contact for 30 minutes, the samples were soaked in natural seawater at the same flow rate for another 10 days to obtain the specimen of Example 2.
[0081] (III) Example 3: Upper limit ratio, mixed gypsum and 0.3 m / s seawater curing Weigh out 1 kg of calcium carbide slag, 1.5 kg of desulfurized gypsum, 1.5 kg of phosphogypsum, 2 kg of silica fume, and 4 kg of slag on a dry basis to obtain 10 kg of all-solid waste cementitious material. Add 4.286 kg of river dredging sand to make the solid waste fine aggregate account for 30% of the total mass of all dry solid raw materials; add 1.4 kg of water, with a water-cement ratio of 0.14, and stir, mold, and cure until final set according to the method in Example 1.
[0082] A dilute sulfuric acid solution with a pH of 3.0 was sprayed onto the surface to be treated in three applications, with a total spraying volume of 2.0 L / m². 2 After reacting for 6 hours, the specimen was gently rinsed with seawater and then statically immersed in natural seawater for 3 days. After removal, the specimen was sprayed with a saturated quicklime solution three times, with a total spray volume of 2.0 L / m², for 1 hour each time, and then immersed in natural seawater at a flow rate of 0.3 m / s for 14 days. Subsequently, it was sprayed with a 0.05 mol / L sodium bicarbonate solution three times, with a total spray volume of 2.0 L / m², for 1 hour each time, and then immersed in natural seawater at the same flow rate for another 14 days, resulting in the specimen of Example 3.
[0083] A cross-sectional sample was taken from the surface of the specimen in Example 3, extending into the matrix. Backscattered electron microscopy combined with energy dispersive spectroscopy was used to scan the sample and observe the continuity of the layers, the connection between the layers and the matrix, and the linear distribution of Ca, Mg, and Cl elements along the depth direction. Figure 4 As shown, due to the high concentration of sodium bicarbonate solution, a distinct outer reaction layer can be observed; and the energy dispersive spectroscopy (EDS) results show that chlorine in seawater, which has a severe corrosive effect on concrete structures, is effectively blocked at the gradient composite anti-corrosion layer, demonstrating that the anti-corrosion layer has good resistance to chloride ion erosion.
[0084] (iv) Comparative Example 1: Immersion in natural seawater only Using the same substrate specimen as in Example 1, but without surface treatment with dilute sulfuric acid, calcium hydroxide alkaline solution, or sodium bicarbonate, the specimen was statically immersed in natural seawater for 27 days to obtain Comparative Example 1 specimen.
[0085] A cross-sectional sample was taken from the surface of the specimen in Comparative Example 1. Backscattered electron microscopy combined with energy dispersive spectroscopy (EDS) was used to observe the continuity of the layer, the connection between the layer and the matrix, and the surface distribution of Mg. Figure 5 As shown in the figure. Energy dispersive spectroscopy (EDS) scans revealed that no anti-corrosion layer was formed on the untreated surface, and the surface substrate was observed to peel off.
[0086] Figure 6Thermogravimetric analysis (TGA) charts are shown for the untreated substrate cured only with seawater (Comparative Example 1 specimen) and the treated substrate cured with seawater (Example 1 specimen). It can be observed that in Comparative Example 1 specimen without the protective anti-corrosion layer, the content of the main hydration product, CASH gel phase (50–120°C range), decreases due to carbonation erosion, while the content of the carbonation product, calcium carbonate (600–700°C range), significantly increases. This indicates that the gradient composite anti-corrosion layer formed by this method can effectively reduce the carbonation erosion of all-solid waste concrete.
[0087] (v) Comparative Example 2: Acidic surface activation omitted Using the same substrate specimen as in Example 1, but without the surface activation with dilute sulfuric acid in step 1 and the first-stage seawater curing, the specimen was directly treated according to steps 2 and 3 of Example 1 to obtain the specimen of Comparative Example 2.
[0088] (vi) Comparative Example 3: Omitted alkaline interface regulation Using the same substrate specimen as in Example 1, step 1 was completed as in Example 1; the left side of the specimen was treated according to steps 2-3 to obtain the specimen of Example 1; the right side of the specimen was not sprayed with saturated quicklime solution in the second stage of step 2, but was only statically soaked in natural seawater for 10 days; then step 3 was completed as in Example 1 to form the specimen of Comparative Example 3.
[0089] Cross-sectional samples were taken at the junction of the left surface of the normally treated specimen (Example 1) and the right surface of the specimen without step 2 (Comparative Example 3). Backscattered electron microscopy combined with energy dispersive spectroscopy was used to observe the continuity of the layer, the connection between the layer and the matrix, and the surface distribution of Mg and Na elements. Figure 7 As shown in the figure. Energy dispersive spectroscopy (EDS) scans revealed that no anti-corrosion layer was formed on the surface where step 2 was not performed, and substrate peeling, crack propagation, and sodium ion enrichment in seawater were observed on that side.
[0090] The performance of the specimens prepared in Examples 1-3 and Comparative Examples 1-3 was tested, and the test results are shown in Table 1.
[0091] Table 1
[0092] Conclusion: As shown in Table 1, Examples 1-3 obtained by the treatment of this invention all formed a gradient composite anti-corrosion layer on the surface of the solid waste concrete matrix, with thicknesses of 18 μm, 20-50 μm, and 54 μm, respectively. All examples exhibited a continuous brucite phase and a structure where unreacted slag particles were surrounded by brucite. The outer reaction layer contained a calcium carbonate phase. Example 1 showed a relatively low calcium carbonate phase content, while Comparative Examples 1-3 did not form the aforementioned continuous brucite phase, particle-surrounded structure, or outer reaction layer. These results indicate that the brucite intermediate layer and the calcium carbonate-containing outer reaction layer formed by this invention can synergistically inhibit the migration of chloride ions and CO2 into the matrix and reduce performance degradation caused by sulfate wet-dry cycles, thereby effectively improving the overall resistance of solid waste concrete to chloride erosion, sulfate erosion, and carbonation erosion.
[0093] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.
Claims
1. A seawater-induced gradient composite anti-corrosion layer on the surface of a solid waste concrete substrate, characterized in that, The seawater-induced gradient composite anti-corrosion layer on the surface of the all-solid-waste concrete substrate includes, sequentially along the direction from the all-solid-waste concrete substrate toward the seawater side: A brucite intermediate layer comprises a brucite continuous phase and unreacted slag particles distributed within the brucite continuous phase. At least a portion of the unreacted slag particles are at least partially surrounded by the brucite continuous phase, and / or the at least a portion of the unreacted slag particles are separated from the solid waste concrete matrix by the brucite continuous phase. The solid waste concrete matrix surface undergoes acid surface activation and a first-stage seawater curing to form a surface microcrack reaction zone, weakening or breaking the solid-phase continuity between at least a portion of the unreacted slag particles and the surrounding matrix. Further alkaline treatment and a second-stage seawater curing then reduce the Mg content in the seawater. 2+ A continuous Mg(OH)2 phase is formed in the surface microcrack reaction zone, and at least some unreacted slag particles are at least partially surrounded by the continuous Mg(OH)2 phase or separated from the solid waste concrete matrix, forming the magnesia intermediate layer. And an outer reaction layer, which is located on the seawater side of the brucite intermediate layer and includes a calcium carbonate phase and a second inorganic reaction phase; the second inorganic reaction phase includes at least one of CASH gel, magnesium aluminum layered bimetallic hydroxide and calcium aluminum layered bimetallic hydroxide.
2. The gradient composite anti-corrosion layer on the surface of the all-solid waste concrete substrate according to claim 1, characterized in that, At least a portion of the unreacted slag particles are surrounded by the continuous brucite phase on their entire outer surface.
3. The gradient composite anti-corrosion layer on the surface of the all-solid waste concrete substrate according to claim 1 or 2, characterized in that, The all-solid-waste concrete matrix is made of all-solid-waste cementitious materials, solid waste aggregates and water. The all-solid-waste cementitious materials, based on a dry basis of 100%, include 5-10% carbide slag, 20-30% industrial by-product gypsum, 5-20% silica fume and the balance being slag; the solid waste aggregates include solid waste fine aggregates.
4. The gradient composite anti-corrosion layer on the surface of the all-solid waste concrete substrate according to claim 3, characterized in that, The solid waste fine aggregate is selected from one or more of iron tailings sand, river dredging sand and gold mine tailings sand, and the solid waste fine aggregate accounts for 10 to 30% of the total mass of all dry solid raw materials in the all-solid waste concrete matrix.
5. The gradient composite anti-corrosion layer on the surface of the all-solid waste concrete substrate according to claim 1, characterized in that, The calcium carbonate phase includes at least one of aragonite and calcite.
6. A method for forming a gradient composite anti-corrosion layer on the surface of a seawater-induced solid waste concrete substrate as described in any one of claims 1 to 5, characterized in that, Includes the following steps: S1, Acidic Surface Activation and First-Stage Seawater Curing: Prepare a solid waste concrete matrix. After the solid waste concrete matrix has set, spray a dilute sulfuric acid solution with a pH of 2.5 to 3.0 onto the surface of the solid waste concrete matrix to be treated, allowing the dilute sulfuric acid solution to react with the surface for 6 hours. Then, place the solid waste concrete matrix in seawater for a first-stage seawater immersion curing for 1 to 3 days, so that a surface microcrack reaction zone is formed within a preset depth from the surface to be treated, and the continuous connection between at least some unreacted slag particles and the solid phase of the surrounding matrix is weakened or broken. S2, Alkaline Interface Regulation and Second-Stage Seawater Curing: After the first-stage seawater immersion curing is completed, an alkaline treatment solution containing calcium hydroxide is sprayed onto the surface to be treated, followed by a second-stage seawater immersion curing lasting 7–14 days, to reduce the Mg content in the seawater. 2+ A continuous Mg(OH)2 phase is formed in the surface microcrack reaction zone, and at least some unreacted slag particles are at least partially surrounded by the continuous Mg(OH)2 phase or separated from the solid waste concrete matrix, forming the magnesia intermediate layer. S3, Bicarbonate Treatment and Third-Stage Seawater Curing: After the second-stage seawater immersion curing is completed, a sodium bicarbonate solution with a concentration of 0.01 to 0.05 mol / L is sprayed onto the surface of the solid waste concrete substrate forming the magnesia intermediate layer. Then, the third-stage seawater immersion curing is carried out for 7 to 14 days, forming an outer reaction layer including a calcium carbonate phase and a second inorganic reaction phase on the seawater side of the magnesia intermediate layer.
7. The forming method according to claim 6, characterized in that, In step S1, a surface microcrack reaction zone is formed at a distance of 0 to 10 μm from the surface of the solid waste concrete matrix. The surface microcrack reaction zone contains at least one of ettringite and gypsum, and can cause some unreacted slag particles to lose their solid-phase continuous connection with the surrounding matrix.
8. The forming method according to claim 6, characterized in that, The seawater is natural seawater, or simulated seawater prepared based on the main ionic composition of natural seawater and containing at least Mg. 2+ SO4 2- and HCO3 - and CO3 2- At least one of the following: The first stage of seawater immersion maintenance adopts static immersion; the second stage of seawater immersion maintenance adopts static immersion or low-velocity immersion with seawater flow velocity greater than 0 and not higher than 0.3 m / s; the third stage of seawater immersion maintenance adopts static immersion or low-velocity immersion with seawater flow velocity greater than 0 and not higher than 0.3 m / s.
9. The forming method according to any one of claims 6 to 8, characterized in that, The alkaline treatment solution containing calcium hydroxide is selected from at least one of saturated quicklime solution and supernatant of carbide slag slurry.
10. The forming method according to claim 6, characterized in that, In step S1, the solid waste concrete matrix is prepared as follows: Based on the total dry weight of the solid waste cementitious material as 100%, 5-10% of carbide slag, 20-30% of industrial by-product gypsum, 5-20% of silica fume, and the remainder of slag are weighed and dry-mixed to ensure uniform dispersion of the powder components. Solid waste aggregate is added and mixing is continued until the solid waste fine aggregate accounts for 10-30% of the total dry solid raw material weight. Water is then added and stirred. The mixture is then poured into a mold for shaping.
Citation Information
Patent Citations
Porous solid material useful for trapping carbon dioxide in seawater comprises a mineral binder, an alkaline earth metal carbonate, an alkaline material and a porogenic material
FR2914301A1
Method for manufacturing carbonic acid solidified steel slag blocks
JP5606596B1